PERANAN MANAJER DALAM MENINGKATKAN KINERJA KARYAWAN PADA PT. ANTARA KESUMA MEDAN - RIANTO RIANTO; AMRIL AMRIL (JURNAL ILMIAH MAKSITEK, 2023)
The purpose of this research is to find out whether the role of the manager has been effective enough in improving the performance of the employees of PT. Antara Kesuma Medan?, and to find out how much influence managers have on the performance of company employees. As well as to know the implementation and benefits of delegation of authority to increase employee motivation in the company. The research method is to obtain relevant data in preparation, the authors conduct research on companies by: (a). library research, namely collecting data by studying books, dictates and other writings that are relevant to the object to be discussed. (b).Field Research (Field Research). This research was conducted by going directly to the field, namely the company to obtain the necessary primary data. To collect the data the research method used was: direct interviews with related parties and direct observation.The results of this study are tasks carried out by subordinates which remain the responsibility of superiors, so that superiors can always provide guidance, direction and supervision of the implementation of tasks. But trust and direction as well as supervision of the implementation of employee duties. With the hope that the trust and expectations given by the manager to employees will arouse the motivation of subordinates to show loyalty for what is entrusted to them. In providing accountability reports, it is done in writing so that subordinates know clearly the boundaries of the implementation of their duties.